The in vitro antigenicity of Plasmodium vivax rhoptry neck protein 2 (PvRON2) B- and T-epitopes selected by HLA-DRB1 binding profile (2018)
Malaria caused by Plasmodium vivax is a neglected disease which is responsible for the highest morbidity in both Americas and Asia. Despite continuous public health efforts to prevent malarial infection, an effective antimalarial vaccine is still urgently needed. P. vivax vaccine development involves analyzing naturally-infected patients' immune response to the specific proteins involved in red blood cell invasion. The P. vivax rhoptry neck protein 2 (PvRON2) is a highly conserved protein which is expressed in late schizont rhoptries; it interacts directly with AMA-1 and might be involved in moving-junction formation. Bioinformatics approaches were used here to select B- and T-cell epitopes. Eleven high-affinity binding peptides were selected using the NetMHCIIpan-3.0 in silico prediction tool; their in vitro binding to HLA-DRB1*0401, HLA-DRB1*0701, HLA-DRB1*1101 or HLA-DRB1*1302 was experimentally assessed. Four peptides (39152 (HLA-DRB1*04 and 11), 39047 (HLA-DRB1*07), 39154 (HLADRB1*13) and universal peptide 39153) evoked a naturally-acquired T-cell immune response in P. vivax-exposed individuals from two endemic areas in Colombia. All four peptides had an SI greater than 2 in proliferation assays; however, only peptides 39154 and 39153 had significant differences compared to the control group. Peptide 39047 was able to significantly stimulate TNF and IL-10 production while 39154 stimulated TNF production. Allele-specific peptides (but not the universal one) were able to stimulate IL-6 production; however, none induced IFN-? production. The Bepipred 1.0 tool was used for selecting four B-cell epitopes in silico regarding humoral response. Peptide 39041 was the only one recognized by P. vivax-exposed individuals' sera and had significant differences concerning IgG subclasses; an IgG2 > IgG4 profile was observed for this peptide, agreeing with a protection-inducing role against P. falciparum and P. vivax as previously described for antigens such as RESA and MSP2. The bioinformatics results and in vitro evaluation reported here highlighted two T-cell epitopes (39047 and 39154) being recognized by memory cells and a B-cell epitope (39041) identified by P. vivax-exposed individuals' sera which could be used as potential candidates when designing a subunit-based vaccine. © 2018 López, Yepes-Pérez, Díaz-Arévalo, Patarroyo and Patarroyo.